Various roasting characteristics against alteration of antioxidant activity, amino acids content, and flavor of Java Ijen-Raung coffee beans - Suud, Hasbi Mubarak (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2023)
The coffee roasting keys are temperature and time. Coffee beans have many chemical and physical reactions while the roasting is running. These reactions are characterized by a pattern in the drying and development phases during coffee roasting. This study discussed how roasting affected the characteristics of coffee beans, particularly antioxidant activity and amino acids, and also tried to define the roasting process by describing each roasting phase. The study discussed these characteristics of Java Ijen arabica coffee, which has speciality coffee criteria. The roasting process can increase amino acids and antioxidant activity inside the coffee beans, but the excessive heat and longer duration of roasting can burn the amino acids. Based on this study, the highest antioxidant Activity was found in beans that had been roasted with a total roasting time under 13 minutes, started with charge temperature of 148oC, and released at 190.5oC. The beans that had been roasted with a total duration under 13 minutes, started with charge temperature of 149oC, and released at 184.8oC is the best roasting degree with the highest score on the cup test.